Bactericidal Effect of Entomopathogenic Bacterium Pseudomonas entomophila Against Xanthomonas citri Reduces Citrus Canker Disease Severity - Villamizar, Sonia; Ferro, Jesus Aparecido; Caicedo, Juan Carlos; Alves, L. M. C. (Frontiers in Microbiology, 2020)
The bacterium Pseudomonas entomophila has been recognized as an exceptional species within the Pseudomonas genus, capable of naturally infecting and killing insects from at least three different orders. P. entomophila ingestion leads to irreversible gut damage resulting from a global blockage of translation, which impairs both immune and tissue repair systems in the insect intestine. In this study we isolated a P. entomophila bacterial strain from soil samples which displayed a strong activity against Xanthomonas citri subsp, citri (Xcc), the etiological agent of citrus canker disease. The antagonism potential of isolated bacteria against Xcc and its ability to reduce citrus canker severity was assessed both ex planta and in planta. Our findings show that pathogenicity assays in Citrus x limonia by pressure infiltration and spray with a mixture of P. entomophila and Xcc leaded to a significant reduction in the number of canker lesions in high susceptible citrus leaves, at 21 days post-infection. To the best of our knowledge this is the first report of antibacterial activity of P. entomophila against a phytopathogenic bacterium. Collective action of P. entomophila factors such as diketopiperazine production and the type 6 secretion system (T6SS) may be involved in this type of biological control of citrus canker. The results suggest that the P. entomophila strain could be a promising biocontrol agent acting directly against Xcc.